Consumer perceptions of environmentally friendly products - M. T. Bendixen; M. Sandler; D. Seligman (South African Journal of Business Management, 1994)
During the past decade, concern for the environment has emerged as a major socio-political Issue among developed nations throughout the world and the increase in the number of environmentally friendly or 'green' products has been significant. The purpose of this exploratory study was to determine the types of products that are considered to be environmentally friendly as well as establishing consumer perceptions of these products. One of the main findings of the research was that 'green' products have achieved substantial awareness among consumers and they are not regarded as a gimmick or a fad. It was also established that the two main barriers that discouraged consumers from purchasing 'green' products were a perception that such products were not price competitive and scepticism regarding their supposed environmental benefits.
Keywords: 650